Prenatal screening and diagnosis of genetic abnormalities: SEGO, SEQCML, AEDP consensus recommendations - Prieto Belén (De Gruyter, 2020)
In this paper, the scientific societies SEGO, SEQCML and AEDP provide a series of consensus-based recommendations for prenatal screening and diagnosis of genetic abnormalities. A set of evaluation indicators are also proposed as a means to improve the quality of the biochemical, ultrasound, and genetic processes involved in prenatal screening and diagnosis of genetic anomalies. Some recommendations are also proposed in relation to invasive prenatal diagnostic procedures, more specifically regarding sample collection and genetic testing. The purpose of this proposal is to unify performance criteria and quality indicators at national level, with audits performed on a regular basis. It is strongly recommended that a national prenatal screening strategy be established and provided with the resources necessary to evaluate the performance of quality indicators and diagnostic procedures under the supervision of health authorities. Protocols should be revised on a regular basis to consider the incorporation of new cost-effective technologies.